The Influence of Brand Image and Adversiting on Daihatsu Car Purchase Decisions at PT. Jujur Jaya Sakti Palopo - Mahmut*, Cici; Nurjannah, Nurjannah; Ardiansyah, Muh.; Talubun, Adryanto; Dandi, Dandi (Universitas Syiah Kuala, 2024)
This study examines the influence of brand image and advertising on the purchase decisions of Daihatsu cars at PT. Jujur Jaya Sakti Palopo. Amidst the increasingly fierce competition in the automotive industry, understanding the factors that influence consumer decisions is crucial for companies. A strong brand image can enhance customer loyalty and support business growth, while effective advertising can attract interest and influence consumer purchasing behavior. This research employs a quantitative approach with a survey design, where data was collected through questionnaires distributed to 100 respondents who had purchased Daihatsu cars at PT. Jujur Jaya Sakti Palopo. The analysis results indicate that both brand image and advertising have a significant impact on purchase decisions, with brand image contributing more significantly. These findings provide important implications for the development of marketing strategies, particularly in brand image management and the optimization of advertising campaigns. Furthermore, this study highlights the importance for companies to strengthen their brand image through various efforts such as improving product quality, after-sales services, and engagement in social activities that can enhance positive consumer perceptions. Additionally, the optimization of advertising, which includes the selection of appropriate media, relevant messaging, and suitable advertising frequency, should also be considered to maximize the impact on consumer purchase decisions. Overall, the results of this study are expected to serve as a guide for PT. Jujur Jaya Sakti Palopo in formulating more effective and efficient marketing strategies, enabling them to compete with other players in the automotive industry.